Reclaiming Freedom While Democracy Decays and AI Surges - Minow, Martha (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2026)
Democratic norms decay as strongmen leaders disable checks on their power; artificial intelligence permeates every sector of societies. Although reflecting different origins and dynamics, these two trends in the first decades of the twenty-first century reflect and escalate social distrust and diminish human capacities. Reclaiming our freedom requires active resistance and actions honouring and deepening our humanity through protest, collaboration, and creativity.